Returns on Sustainable Mutual Funds in India - Jain, Anant (2011)
The world has seen a huge growth in investment through the sustainable sector. But the study on the cost in construction and measuring the performance of such investments is confined to the limited countries. Thus to compare the performance of the sustainable investment with that of traditional investments it is necessary to increase the sample size of the study. Considering this in mind the paper aims to study the performance and risk of the sustainable mutual fund investments with that of traditional mutual funds in Indian market. This is been done by constructing a portfolio of ethical funds and the traditional mutual funds, taking into consideration the highest Sharpe ratio. The performance of the SRI mutual fund is been compared with that of conventional mutual fund with the help of Jensen’s alpha. This test are further checked with the help of three factor model as used by Baure, R.; Derwall, J. and Otten, R. (2006) etc. In our study we also try to see what the main problems that doesn’t allow the ethical investor to become the mainstream investor.